2021
DOI: 10.1101/2021.03.02.21252772
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying impacts of the COVID-19 pandemic through life expectancy losses: a population-level study of 29 countries

Abstract: The COVID-19 pandemic halted longevity improvements and mortality reductions at older ages in 2020. Life expectancy at birth - a widely-used indicator of population health - declined from 2019 to 2020 in 24 out of 26 countries for which high-quality vital statistics are presently available, including most European countries, Chile and the USA. Males in the USA and Bulgaria experienced the largest losses in life expectancy at birth during 2020 (2.1 and 1.6 years respectively), but staggering reductions of more … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 44 publications
3
38
1
8
Order By: Relevance
“…Our estimates of the loss of life expectancy in Switzerland in 2020 are close to those obtained by Aburto et al [8], who reported a loss of almost 12 months for men, and slightly more than 6 months for women. Of note, these results were calculated using five broad age classes (0-14, 15-64, 65-74, 75-84, and 85+).…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…Our estimates of the loss of life expectancy in Switzerland in 2020 are close to those obtained by Aburto et al [8], who reported a loss of almost 12 months for men, and slightly more than 6 months for women. Of note, these results were calculated using five broad age classes (0-14, 15-64, 65-74, 75-84, and 85+).…”
Section: Plos Onesupporting
confidence: 90%
“…Heuveline and Tzen [ 7 ] applied a similar procedure for 186 countries or territories, including Switzerland. In a preprint, Aburto et al [ 8 ] provided such estimates for 29 countries, including Switzerland, based on all-cause mortality. Given the potential importance of such analyses in the current (urgent) scientific and political debates on the COVID-19 pandemic, we believe that even results that are not entirely definitive deserve to be presented and published.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of other death rates that increased during the COVID-19 pandemic, such as unintentional injuries, because they tend to be at younger ages than COVID-19 deaths, equating excess deaths to unreported COVID-19 would lead to some underestimation of years of lost life and, as a result, MUL. A similar gap can be observed considering estimates of changes in PLEB that are now available in a number of nations [45] and that differ more from initial estimates based on reported COVID-19 deaths only [46] than excess to COVID-19 death ratio would have suggested.…”
Section: Plos Onesupporting
confidence: 57%
“…If the modeling goal is mortality forecasting, as under the counterfactual no-COVID scenario, then fitting seasonal regression models over all weeks of a year reduces the bias in the forecasted death counts. A lack of adjustment for continuous mortality improvements, as have been observed across Europe up until 2020 [15,2], explains the tendency of the average death rate model towards low estimates of excess. By simply averaging declining death rates over time, one overestimates expected mortality for the current year, thus underestimating excess.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of adjustment for continuous mortality improvements, as have been observed across Europe up until 2020 [15, 2], explains the tendency of the average death rate model towards low estimates of excess. By simply averaging declining death rates over time, one overestimates expected mortality for the current year, thus underestimating excess.…”
Section: Discussionmentioning
confidence: 99%